2015
DOI: 10.1111/febs.13601
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania hijacking of the macrophage intracellular compartments

Abstract: Leishmania spp., transmitted to humans by the bite of the sandfly vector, are responsible for the three major forms of leishmaniasis, cutaneous, diffuse mucocutaneous and visceral. Leishmania spp. interact with membrane receptors of neutrophils and macrophages. In macrophages, the parasite is internalized within a parasitophorous vacuole and engages in a particular intracellular lifestyle in which the flagellated, motile Leishmania promastigote metacyclic form differentiates into non-motile, metacyclic amastig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 121 publications
0
27
0
Order By: Relevance
“…Similarly to other exosome markers, such as the heat shock proteins HSP70 and HSP90 (43,61) and the L. major virulence factor P46 (65,66), HA 3 -LmPRL-1 was identified inside the cytoplasm of infected macrophages and colocalized with the late phagosomal marker LAMP-1 on the surfaces of PV, where it is ideally positioned to manipulate host cell signaling pathways in favor of the parasite (67). It is possible that LmPRL-1 directly modulates the phosphorylation status of host signaling molecules and thereby also synergizes with other secreted virulence factors of L. major.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly to other exosome markers, such as the heat shock proteins HSP70 and HSP90 (43,61) and the L. major virulence factor P46 (65,66), HA 3 -LmPRL-1 was identified inside the cytoplasm of infected macrophages and colocalized with the late phagosomal marker LAMP-1 on the surfaces of PV, where it is ideally positioned to manipulate host cell signaling pathways in favor of the parasite (67). It is possible that LmPRL-1 directly modulates the phosphorylation status of host signaling molecules and thereby also synergizes with other secreted virulence factors of L. major.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that host cell receptors (for example Complement receptors and Fcγ) influence L. donovani internalization and this interaction is partially dependent on the presence of promastigote flagella [49]. It is also documented that host cell membrane microdomains influence internalization of the parasite [5,7,50] . In order to hijack the cellular defense machinery L. donovani interacts with components of endoplasmic reticulum and the trans-Golgi network (TGN) [7,51].…”
Section: Intracellular Life Of L Donovani: the Role Of Wnt5a Signalimentioning
confidence: 99%
“…L. donovani invades mostly host macrophages and also dendritic cells and neutrophils, hijacking the cellular machinery for its survival through adopting various strategies to evade immune response [5]. One of the strategies employed by the parasite is to inhibit phagolysosomal maturation by altering host cell lysosomal integrity [6].…”
Section: Introductionmentioning
confidence: 99%
“…This Minireview series on Intracellular Pathogens describes the intra-macrophagic escape and survival mechanisms developed by very different intracellular pathogens: the bacteria of the Chlamydiales order [1], the parasite Leishmania [2] and the fungus Histoplasma capsulatum [3]. All three pathogens are internalized into macrophages by receptor-mediated endocytosis, involving specific receptors for each microorganism [4][5][6].…”
mentioning
confidence: 99%
“…The Minireviews in this series discuss the recent advances in understanding the complex dance between microorganism and macrophage [1][2][3]. Importantly, they highlight the common strategies employed by each pathogen to circumvent host defense, and as such will be useful in considering future therapeutic angles.…”
mentioning
confidence: 99%